Faktor-Faktor Yang Berhubungan dengan Terjadinya Sisa Makanan Pasien Diabetes Mellitus Di Rumah Sakit Umum Daerah Dr. H. Moch. Ansari Saleh Banjarmasin - Yuliana Salman; Rissa Saputri; M. Rasyid Ridha; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Non-compliance diabetes mellitus patients to the diet can be seen from the many leftover food. Leftover food is one indicator ofthe success of nutrition services in the in patient unit. Leftovers food occurs because patients do not spend on food that has been given. The maincause of external factors and internal factors, but there are other factors that caused leftovers is food quality factors consisting of a food variety, food appearance and taste of food is also one causes of leftover food. This researchaimed to know the factors related with the occurrence leftovers food of diabetes mellitus patients in Dr. H.Moch. Ansari Saleh Hospital Banjarmasin. The research design was across sectional survey approach. Sample was 45 patients with diabetes mellitus who are under going treatment in the Safir room and Nilam room. The statistical testused was a Chi-Square. Research result shows that respondents who expressed a variety of food is satisfactory (88,9%), food appearance was satisfactory (84,4%), taste the food was satisfactory (66,7%), the average leftovers food of patient remain many (>25%) on the type of vegetableside dish that is equal to 55,6%, animal side dish and fruit of 51,1% and average leftovers food of patient overall remain many (>25%) is equal to(55,6%). Chi-Square test results showed no correlation between variety of food and food appearance with leftovers food (p >0,05), while the taste of the food has a significant correlation with the leftovers food (p <0,05).